PSYCHOLOGICAL FACTORS OF INTERNET ADDICTION AMONG STUDENTS - Otamurodova Zarina Egamberdi kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the psychological consequences of internet addiction among students and its impact on mental health and educational effectiveness. During the research, issues such as stress, anxiety, reduced concentration, and social problems caused by excessive internet use were highlighted. In addition, recommendations for preventing internet addiction were provided.